Naïve and expert geography students' perceptions on digital map literacy - (:unkn) unknown (University of Toronto Press, 2005)
The aims of this comparative study are first to analyze the Digital Map Literacy (DML) perceptions of undergraduate geography students, and second to compare the perceptions of naive and expert students on a web based atlas. The students were selected from the Department of Geography Education at Marmara University in Istanbul. The DML scale was used to collect the data from the students. The data, including students' perceptions were analyzed and compared according to their experience levels (expert or naive) on map literacy and computer literacy. Students were classified as expert and naive on map literacy and computer literacy based on their own expression on the scale. Also, the DML perceptions of the student groups have been compared with three different perspectives: (1) cultural-aesthetical dimension: visual perception, (2) technical-informational dimension: functional perception, (3) geographical-social dimension: map perception. The data obtained has been transferred to statistics SPSS software and the findings have been analyzed within these data. At the scope of Encarta Reference Library 2003 application program, the groups' perceptions have been compared with X2 test on a single item base and independent t- test samples in general. The results showed that there are no significant differences between the expert and the naive student groups' perceptions on the DML at 0.05 level of significance. The groups' perceptions bounded with literacy experience are the same in the digital atlas utilization on the web. Based on the Digital Map Literacy scale, it can be said that the Microsoft Encarta digital atlas provides affordance, visibility, utility, functionality, ease of use, and simplicity to the naives and the experts geography students. This result indicated that effective usability design is important to increase efficiency, productivity and understandability of the digital atlases on the web. © University of Toronto Press.
Keywords: Assessment; Atlas; Digital Map Literacy (DML); Expert; Geographical Information Systems (GIS); Naive; Perception